2011
DOI: 10.15560/7.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Gastropods from Camamu Bay, state of Bahia, Brazil

Abstract: The present study provides a species list of marine and estuarine gastropods from Camamu Bay, in the state of Bahia, northeastern Brazil. Expeditions to collect mollusks were carried out between 2003 and 2006 in Acaraí River estuary, using a trawling boat with otter trawl. A total of 3,193 gastropod specimens were identified, belonging to 46 families, comprising 94 species. Amongst the recorded species, all represent the first occurrence to Camamu Bay and four to the state of Bahia (genera Littoridina, Morula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…All bivalve species identified are filter feeders (see Rios 2009). Cerithiidae and Neritidae are among the most abundant families of herbivorous caenogastropods sampled from coastal environments of Brazil (Rios 2009, Ourives et al 2011, Duarte et al 2014, Longo et al 2014. Neritina virginea and Cerithium atratum were the most abundant herbivorous gastropods collected in the present study, both of which are commonly found associated with seagrass (see Longo et al 2014, Duarte et al 2015.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…All bivalve species identified are filter feeders (see Rios 2009). Cerithiidae and Neritidae are among the most abundant families of herbivorous caenogastropods sampled from coastal environments of Brazil (Rios 2009, Ourives et al 2011, Duarte et al 2014, Longo et al 2014. Neritina virginea and Cerithium atratum were the most abundant herbivorous gastropods collected in the present study, both of which are commonly found associated with seagrass (see Longo et al 2014, Duarte et al 2015.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, neogastropods of the families Columbellidae, Melongenidae, Muricidae, Nassariidae and Olivellidae are among the main carnivorous and/or scavenger gastropod groups living in estuarine regions (Rios 2009, Ourives et al 2011. Only one species of each family was found in the material studied, although these groups are usually more numerous in other Brazilian estuarine ecosystems (see Rios 2009, Ourives et al 2011. The columbellid Parvanachis obesa was the most abundant neogastropod collected from the estuary of the Paraíba River.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations